Identification of Specific Cell Surface Markers on Immune Cells of Squirrel Monkeys (Saimiri sciureus) - Bharti P. Nehete; Ashley DeLise; Pramod N. Nehete (Journal of Immunology Research, 2024)
Nonhuman primates are an important experimental model for the development of targeted biological therapeutics because of their immunological closeness to humans. However, there are very few antibody reagents relevant for delineating the different immune cell subsets based on nonhuman primate antigens directly or with cross-reactivity to those in humans. Here, we report specific expression of HLA-DR, PD-1, and CD123 on different circulating immune cell subsets in the peripheral blood that included T cells (CD3+), T cells subsets (CD4+ and CD8+), B cells (CD20+), natural killer (NK) cells (CD3–CD16+), and natural killer T cells (CD3+CD16+) along with different monocyte subsets in squirrel monkey (Saimiri sciureus). We established cross-reactivity of commercial mouse antihuman monoclonal antibodies (mAbs), with these various immune cell surface markers. These findings should aid further future comprehensive understanding of the immune parameters and identification of new biomarkers to significantly improve SQM as a model for biomedical studies.